2006
DOI: 10.1186/1471-2407-6-269
|View full text |Cite
|
Sign up to set email alerts
|

Intensive post-operative follow-up of breast cancer patients with tumour markers: CEA, TPA or CA15.3 vs MCA and MCA-CA15.3 vs CEA-TPA-CA15.3 panel in the early detection of distant metastases

Abstract: Background: In breast cancer current guidelines do not recommend the routine use of serum tumour markers. Differently, we observed that CEA-TPA-CA15.3 (carcinoembryonic (CEA) tissue polypeptide (TPA) and cancer associated 115D8/DF3 (CA15.3) antigens) panel permits early detection and treatment for most relapsing patients. As high sensitivity and specificity and different cut-off values have been reported for mucin-like carcinoma associated antigen (MCA), we compared MCA with the above mentioned tumour markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 43 publications
1
29
0
5
Order By: Relevance
“…Among the numerous serum markers that have been investigated as potential predictors of clinical outcome in breast cancer patients, the most widely used are CA 15-3 and CEA (25,26). Some authors have already reported on RANK-L and OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Among the numerous serum markers that have been investigated as potential predictors of clinical outcome in breast cancer patients, the most widely used are CA 15-3 and CEA (25,26). Some authors have already reported on RANK-L and OPG.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these values remained high in the leave-one-out cross-validation, proving the robustness of our classifier. More remarkably, our autoantibody panel allows a diagnosis improvement in CIS samples with a better accuracy than other biomarkers (i.e., CA15-3 and CEA) currently used in clinical practice (35). Recently, Chapman et al showed that, taken separately, each of the seven markers (p53, c-myc, HER2, NY-ESO-1, BRCA1, BRCA2, and MUC1) was present in a maximum of 23% of patients with ductal CIS, whereas the combination of the seven markers enabled detection of this cancer in 45% of the affected patients (5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that serial determination of CA 15-3 and CEA levels during the postoperative follow-up of breast cancer patients may be useful for early detection of preclinical recurrence or metastatic disease (8,9). In addition, the serum levels of CA 15-3 and CEA may be used to predict response to chemotherapy in patients with metastatic breast cancer (MBC) (10).…”
Section: Introductionmentioning
confidence: 99%